Comprehensive Obstetric Care In Ny "Y" With Oxytocin Massage Intervention Against Uterine Involution In Postpartum Mothers - Enderia Sari; Echa Muthia Indrianti (Jurnal Inspirasi Kesehatan, 2023)
The number of maternal mortality in South Sumatra Province in 2020 is 128 people per 100,000 live births. The highest cause of death in mothers was bleeding by 42 people (31.25%). Bleeding can be prevented if the mother's uterine contractions are good. Uterine contractions are both obtained from the hormone oxytocin. The hormone oxytocin can be obtained from oxytocin massage. The goal is to provide obstetric care to Mrs. "Y" comprehensively. From the period of pregnancy, childbirth, puerperium, by applying oxytocin massage The method used is a case study, the subject of this report is postpartum mothers the application of oxytocin massage is carried out 2x a day for 7 consecutive days since giving birth. Data collection techniques through interviews, observations, physical examinations, SOAP forms, giving questionnaires to patients before oxytocin massage and after oxytocin massage. The result is that after comprehensive obstetric care, the mother did not experience any dangerous cases. The labor process takes place normally, during the puerperium there are no special complaints that are dangerous, the mother is given oxytocin massage for 7 days postpartum in a duration of 10-15 minutes. The results of the study on Mrs. "Y" there was a significant influence of uterine involution when the mother was given oxytocin massage. On day 7, the decrease in uterine fundal height occurred faster than in mothers who did not do oxytocin massage. In conclusion, oxytocin massage care affects the decrease in fundus height of the uteri.